Pertumbuhan dan Uji Organoleptik Tanaman Sawi Hijau Hasil Biofortifikasi Kalsium yang diBudidayakan Secara Hidroponik - Reza Elsadai Silalahi; Munandar Munandar; Teguh Achadi; Fitra Gustiar; Nura Malahayati (xxxx-xxxx, 2020)
Silalahi RE, Munandar M, Achadi T, Gustiar F, Malahayati N. 2020. Growth and organoleptic test of green mustard biofortification results of calcium cultivated hydroponic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The low calcium intake of the Indonesian people is one of the causes of the high risk of osteoporosis. Therefore, support is needed to meet the body's calcium needs. This study aims to determine the growth and organoleptic test of mustard greens (Brassica juncea L.) as a result of biofortification with calcium (Ca) cultivated hydroponically by floating rafts. This study used a descriptive test with 2 treatments and 4 replications, consisting of 0 ppm (P0) control treatment and 300 ppm calcium (P1) treatment of mustard plants. The parameters observed included plant height, number of leaves, level of greenness, plant fresh weight, plant dry weight, moisture content, root crown ratio, calcium content, food fiber and organoleptic tests with components of assessment of color, taste, preference, and texture. The research treatment did not significantly affect plant growth seen from the height of the mustard greens with calcium treatment, only a slight decrease from the control mustard plant, but it greatly affected plant production as seen from the wet weight and dry weight of the control mustard plant which had a higher weight than the mustard plant with calcium. Giving a calcium concentration of 300 ppm increased the number of leaves, greenness of the leaves, increased calcium content and dietary fiber in mustard greens. The assessment of the organoleptic test results showed that mustard greens with calcium treatment were dark green, had a sweet taste, had a crunchy texture, and were preferred by panelists. So the mustard plants that get the addition of 300 ppm of calcium can be accepted and liked by the community to meet their daily calcium needs.